Effect of planting geometry and intercropping on growth attributes, leaf yield, quality of mulberry (Morus alba) and its economics under irrigated, Gangetic alluvial soil conditions - SETUA, G C; MISRA, A K; KAR, R; SHIVNATH, SHIVNATH; DATTA, R N; GHOSH, A (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted under irrigated condition to study the effect of planting geometry and intercropping on growth characters, leaf yield and quality in newly evolved, triploid, high yielding, recommended and popular S 1635 mulberry (Morus alba L.) along with intercrop yield and additional net profit. The plants were established through saplings in seven different spacing with variable number of plants / ha and were maintained through recommended package of practices for irrigated garden. Four different suitable intercrops, one in each season and one green manure crop in July September were taken up annually in mulberry for judicious utilization of space, time, nutrients and also for soil enrichment.      Significant differences were observed among the treatments in all the parameters studied. Growth attributes and leaf quality were improved along with soil nutrient status in paired row system, particularly in (90cm + 120cm) × 60cm spacing. Besides, it registered almost similar leaf yield (29 488.98kg/ha/year) compared to 60cm × 60cm spacing (control) in spite of 42.9% less plant population (15 873/ha) over control (27 777/ha), higher leaf yield / plant (0.37kg) and optimum intercrop yield as well as additional net profit of r35 368/ha/year (r5974.00 more over control).      Hence, this paired row spacing [(90cm + 120cm) × 60cm] may be useful and recommended to the farmers for mass practice in the cultivation of S 1635 mulberry with four intercrops and one green manure crop / year at least up to three years which did not adversely affect mulberry under irrigated condition. In addition, there is also a scope for partial mechanization which enables to reduce manpower requirement as well as economy in cultivation.